2014
DOI: 10.13005/ojc/300317
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Sequence of Borane Series

Abstract: A table of hydroborane families has been created. The table links boranes of different families(homologous series) and members of the same family based on k number. The table is useful deducing straight away whether a borane( molecular formula) is closo, nido or arachno or something else. The table also indicates that boranes are formed according to natural periodic function (arithmetical progression). The empirical formula utilized is extremely versatile, simple and based on the principle of Nobel gas configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The cluster number, k-value for a carbonyl cluster is calculated [1][2][3][4][5] using the empirical formula k = ½ (E-V). By analyzing the cluster numbers, it has been possible to discern the latent infinite world of series of clusters for elements which obey the 18-electron rule or 8-electron rule(octet rule).…”
mentioning
confidence: 99%
“…The cluster number, k-value for a carbonyl cluster is calculated [1][2][3][4][5] using the empirical formula k = ½ (E-V). By analyzing the cluster numbers, it has been possible to discern the latent infinite world of series of clusters for elements which obey the 18-electron rule or 8-electron rule(octet rule).…”
mentioning
confidence: 99%
“…M-3-3-48-o A. Hence the cluster, Os 3 (CO) 12 belongs to the arachno series. The shape of the cluster is a trigonal planar.…”
Section: Categorization Of a Cluster Formulamentioning
confidence: 95%
“…The Wade-Mingos rules have been extremely helpful in deducing the cluster geometries (Mingos, 1984;Wade, 1976;Jemmis, 1984Jemmis, ,2002Jemmis, ,2003Jemmis, ,2005Jemmis, ,2006Jemmis, ,2008King, 2002;Welch, 2013). Furthermore, it has been found that carbonyl clusters and some main group clusters can be categorized using 4n and 14n series (Kiremire, 2014(Kiremire, , 2015. Since the 14n series (14n±q) run parallel to 4n series (4n±q), the 4n series can be used instead of the 14n series.…”
Section: Introductionmentioning
confidence: 99%
“…This is because it is easier to use 4n rather than 14n series. We have also demonstrated that the 14n and 4n series can be used to categorize and predict shapes of clusters of carbonyls, boranes and heteroboranes (Kiremire, 2014(Kiremire, ,2015. In this paper, a numerical sequences based on 14n series that give precise valence contents of clusters and their arrangements into series is presented.…”
Section: Introductionmentioning
confidence: 99%